Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12888-020-02933-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective prediction of PTSD diagnosis in a nationally representative sample using machine learning

Abstract: Background Recent research has identified a number of pre-traumatic, peri-traumatic and post-traumatic psychological and ecological factors that put an individual at increased risk for developing PTSD following a life-threatening event. While these factors have been found to be associated with PTSD in univariate analyses, the complex interactions of these risk factors and how they contribute to individual trajectories of the illness are not yet well understood. In this study, we examine the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 59 publications
(63 reference statements)
1
9
1
Order By: Relevance
“…Although compared to males and older age groups, females and the younger age group expressed a higher prevalence of PTSD symptoms, the difference was slight and not significant. This conflicts with previous studies, where females and younger age groups were indicated to be more likely to express mental health problems, including likely PTSD symptoms, compared to males and older age groups [44][45][46][47][48]. Since our study sample size was relatively small, it may not have elicited that difference as reported in other studies.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Although compared to males and older age groups, females and the younger age group expressed a higher prevalence of PTSD symptoms, the difference was slight and not significant. This conflicts with previous studies, where females and younger age groups were indicated to be more likely to express mental health problems, including likely PTSD symptoms, compared to males and older age groups [44][45][46][47][48]. Since our study sample size was relatively small, it may not have elicited that difference as reported in other studies.…”
Section: Discussioncontrasting
confidence: 82%
“…The majority of respondents who had a depression history (67.3%) reported having likely PTSD symptoms after the flood. This finding is highly consistent with research on the main effects of prior mental health disorders on PTSD [3,45,[49][50][51][52]. Much research has determined a relationship between depression and PTSD among those who have experienced trauma, including natural disasters, childhood maltreatment, serious accident, or terrorist act [53][54][55].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Obviously plausible is, of course, the notion of diagnostic overlap between PTSD and frequent comorbid diagnoses, as depression or anxiety. Recent progress in prospective research designs (DiGangi et al, 2013 ; Worthington, Mandavia, & Richardson-Vejlgaard, 2020 ) additionally supports the pre-dispositional model (McFarlane, 2004 ) assuming that especially individuals suffering from specific pre-existing disorders may develop symptoms of posttraumatic stress following the experiences of potentially traumatic events.…”
Section: Introductionmentioning
confidence: 96%
“…16,17 Although several studies have applied ML algorithms to predict PTSD, our study is distinct because these studies focused on pure prediction of PTSD rather than estimating effect heterogeneity, which is our focus. [18][19][20][21] We leveraged a unique natural experiment setting stemming from the 2011 Great East Japan Earthquake and Tsunami, where a longitudinal cohort study of Japanese older adults established 7 months before the earthquake onset offered an opportunity to collect rich predisaster data of the survivors. 22…”
mentioning
confidence: 99%